Cutaneous tumours of vascular origin: two rare entities - Prakash, Annu E.; Sulochana, Gopalan; Thankappan, Thundiparampil; Oommen, Annamma M. (International Journal of Research in Medical Sciences, 2019)
Skin and subcutaneous tissue are the most common location of benign and malignant vascular tumors. The benign or malignant nature of the lesion may not always be identified clinically because of the varying presentations. The histology of the lesion, especially in malignancies may not exhibit definite vascular pattern. In such cases, clinical presentation has to be correlated with histopathological picture as well as immunohistochemical characteristics to reach a specific diagnosis. Judicious use of immunohistochemical markers proves to be invaluable. Two rare cases of cutaneous vascular tumors which presented at our institution are cited, the diagnosis of which involved correlation of these modalities.